2022
DOI: 10.1039/d1cc06991h
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanistic investigation of B12-independent glycerol dehydratase and its activating enzyme GD-AE

Abstract: B12-independent glycerol dehydratase (GD) is a glycyl radical enzyme in the biotransformation of glycerol to 1,3-propanediol. GD requires the activating enzyme GD-AE to initiate the radical reaction. GD-AE belongs to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Interestingly, the special SAM cleavage activity of Dph2 resulted from the distinct geometry of SAM binding with 4Fe-4S, which was conjugated by three cysteines from different domains of the protein instead of the CxxxCxxC motif. 25 The Broderick group 27 and our group 28 recently demonstrated that glycerol dehydrogenase-activating enzyme GD-AE, the only previously assumed noncanonical radical SAM enzyme with the CxxxCxxC motif, is a canonical radical SAM enzyme that generates the 5′-dA radical. Moreover, many enzymes, such as TWY2 29 , Tsr3 30 and AzeJ 31 , cleave the C γ,Met -S bond of SAM by a nucleophilic mechanism.…”
mentioning
confidence: 99%
“…Interestingly, the special SAM cleavage activity of Dph2 resulted from the distinct geometry of SAM binding with 4Fe-4S, which was conjugated by three cysteines from different domains of the protein instead of the CxxxCxxC motif. 25 The Broderick group 27 and our group 28 recently demonstrated that glycerol dehydrogenase-activating enzyme GD-AE, the only previously assumed noncanonical radical SAM enzyme with the CxxxCxxC motif, is a canonical radical SAM enzyme that generates the 5′-dA radical. Moreover, many enzymes, such as TWY2 29 , Tsr3 30 and AzeJ 31 , cleave the C γ,Met -S bond of SAM by a nucleophilic mechanism.…”
mentioning
confidence: 99%
“…Given not only the value of fluorine-containing compounds for drug discovery but also an emerging interest in organosilanes for this purpose, silicon-substituted fluorohydrins could present a novel platform for designing conformationally restricted biologically active structures. Alternatively, oxidative desilylation would generate 2-fluoro-1,3-propanediols, which have proven to be useful for studying enzymatic reactions involving glycerol , as well as starting points to access fluorinated carbohydrate analogues of medicinal value . To that end, Tamao–Fleming oxidation of the 3-silyl fluorohydrin products was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the special SAM cleavage activity of Dph2 results from the distinct geometry of SAM binding with 4Fe-4S, which is ligated by three cysteines from different domains of the protein instead of the CxxxCxxC motif. 24 The Broderick group 26 and our group 27 recently demonstrated that glycerol dehydrogenase-activating enzyme GD-AE, the only previously assumed noncanonical RS enzyme with the CxxxCxxC motif, 28 is a canonical RS enzyme that generates the 5′-dA radical. Moreover, many enzymes, such as TWY2, 29 Tsr3 30 and AzeJ, 31 cleave the C γ,Met −S bond of SAM by a nucleophilic mechanism.…”
mentioning
confidence: 99%